The Impact Of Festivals In Promoting Cultural Tourism: A Case Study On Gopalpur Beach Festival, Odisha. (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Fairs and festivals are important part of life. It contributes peace and imparts  relaxation, pleasure to human being. In India we observe number of festivals throughout the year.  Odisha is known for its festivals and folk cultures. In Odisha different fairs and festivals attract  culture tourists and promote tourism in the state. Objective: The objective of the study is to identify  the important attributes to attract tourists at GopalPur beach festival of Odisha. Methodology:  The study was conducted by taking 100 tourists as the sample size. The survey questionnaires were  administered along with face to face interviews with the tourists or the respondents. A 5-Point  Likert scale was used to measure tourist’s satisfaction. Results: The findings of this research  revealed that attributes like Art and Craft, Sand Art, Local community etc. had contributed in the  development of GopalPur Beach festival of Odisha. Conclusion : Cultural tourism can thus help in  the economic and social development of the state.
Keywords: Impact; Festivals; Culture; Tourism; Economy